2014
DOI: 10.1007/s10620-014-3419-5
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of Long-Term Maintenance Treatment with Azathioprine Tends to Increase Relapse Risk in Patients with Crohn’s Disease

Abstract: AZA withdrawal resulted in a significantly increased relapse risk after 1 year and a nonstatistically significant trend for relapse after 2 years. Our results are in line with previous observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
0
36
0
1
Order By: Relevance
“…These comprised 5 RCTs 8-12 and 13 retrospective cohort studies [13][14][15][16][17][18][19][20][21][22][23][24][25] (one of which 20 was an extension study from a previous RCT 8 ). Eleven studies reported on immunomodulator withdrawal in CD [8][9][10][11]14,15,17,20,[23][24][25] and 8 in UC. 12,13,[17][18][19]21,22,24 One study by Fraser et al reported on long-term outcomes of patients treated with methotrexate and presented relapse rates for IBD with no distinction between CD and UC.…”
Section: De-escalation Of Immunomodulator Monotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…These comprised 5 RCTs 8-12 and 13 retrospective cohort studies [13][14][15][16][17][18][19][20][21][22][23][24][25] (one of which 20 was an extension study from a previous RCT 8 ). Eleven studies reported on immunomodulator withdrawal in CD [8][9][10][11]14,15,17,20,[23][24][25] and 8 in UC. 12,13,[17][18][19]21,22,24 One study by Fraser et al reported on long-term outcomes of patients treated with methotrexate and presented relapse rates for IBD with no distinction between CD and UC.…”
Section: De-escalation Of Immunomodulator Monotherapymentioning
confidence: 99%
“…All 4 RCTs in CD reported higher relapse rates after stopping the immunomodulator compared with continuing the drug. [8][9][10][11] All RCTs focused on azathioprine exclusively and the longest follow-up was for 2 years after withdrawal. 10 The study by Lemann et al was designed as a noninferiority study, and the investigators concluded that they could not reject the hypothesis that placebo was inferior to continuing azathioprine.…”
Section: De-escalation Of Immunomodulator Monotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…7 15 NS NR 8 of 15 (Vilien, et al, 2004) (Gross, et al, 1998) 13 1 NS Less than 1 year 0 of 1 (Lennard-Jones, 1977) 14a 11 C 3 months to 2 years 6 of 11 (Prantera, et al, 1992) 14b 18 IC 3 months to 2 years 9 of 18 (Prantera, et al, 1992) 14c 32 I 3 months to 2 years 17 of 32 (Prantera, et al, 1992) (Gendre, et al, 1993) 21b #48 NS 3 months to 2 years 22% 42% (Gendre, et al, 1993) 22 101, 57 NS 1 -2 years or less 36 of 101 34 of 57 (Summers, et al, 1979) 23a 7 C 12 months or more 0 of 7 (Wenzl, et al, 2015) 23b 14 IC 12 months or more 7 of 14 (Wenzl, et al, 2015) 23c 5 I 12 months or more 1 of 5 (Wenzl, et al, 2015) 24 § § § § ~ 65% (Malchow, et al, 1984) 25 #10 NS NR 50% (Nyman, et al, 1985) (Steenholdt, et al, 2012) 9 100 95 4% 7% 12% 20% 27% 48% NR (Papamichael, et al, 2015) …”
mentioning
confidence: 99%